Praktik Pembuatan Hand sanitizer Sebagai Upaya Pencegahan Penyakit yang Diakibatkan oleh Virus - Elisma Elisma; Yuliawati Yuliawati; Fitrianingsih Fitrianingsih; Fathnur Sani K; Revis Asra (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2022)
Using of hand sanitizers is an important step in preventing the spread of the virus, but the proliferation of new hand sanitizers that do not meet standards demands that people choose wisely. The existence of a policy that the community may make their own hand sanitizers also needs to be balanced with an increase in people's understanding of how to make them correctly. Activity starting with coordination, preparation, implementation and evaluation through question and answer. This service was preceded by counseling about infectious diseases how to prevent them. One way to prevent it is washing hands properly. Firstly, choose soap, but if difficult to get water, a hand sanitizer is a solution. Furthermore, counseling about hand sanitizers in the form of selecting hand sanitizers according to standards, making hand sanitizers through video presentation and proper hand washing methods. Team makes hand sanitizers at the Biotechnology and Engineering Laboratory for the implementation of sterilization to labeling. The video shows the preparation stages in the form of sterilizing the equipment, measuring, mixing, filling, packaging and labeling. The community is given hand sanitizer samples as well so that people can see examples of hand sanitizer labels and important components that should be there. During the question and answer session, most of them answered correctly, were able to choose and understand hand sanitizer formulas meet standards requirement and knew how to wash their hands properly so that it was hoped that they could prevent diseases caused by viruses.